2020
DOI: 10.1186/s12974-020-01819-z
|View full text |Cite|
|
Sign up to set email alerts
|

A primary neural cell culture model to study neuron, astrocyte, and microglia interactions in neuroinflammation

Abstract: Background: Interactions between neurons, astrocytes, and microglia critically influence neuroinflammatory responses to insult in the central nervous system. In vitro astrocyte and microglia cultures are powerful tools to study specific molecular pathways involved in neuroinflammation; however, in order to better understand the influence of cellular crosstalk on neuroinflammation, new multicellular culture models are required. Methods: Primary cortical cells taken from neonatal rats were cultured in a serum-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(147 citation statements)
references
References 104 publications
7
139
0
1
Order By: Relevance
“…Experimental models have also shown that overactive GSK3β is also associated with reactive astrocytosis and microgliosis, an effect that may also be attenuated by lithium (Tang et al, 2016). In a recent study conducted by our group, we showed that that chronic treatment with lithium chloride at subtherapeutic concentrations was able to modify the secretion of pro-and anti-inflammatory interleukins in cocultures of cortical and hippocampal neurons with glial cells, and this effect was associated with the preservation of culture integrity (De-Paula et al, 2016b;Goshi et al, 2020). Gene Ontology (GO) is a bioinformatics approach to ascertain and to unify the representations of gene-and gene product attributes across species, focusing on the related functions of these interactions.…”
Section: Introductionmentioning
confidence: 86%
“…Experimental models have also shown that overactive GSK3β is also associated with reactive astrocytosis and microgliosis, an effect that may also be attenuated by lithium (Tang et al, 2016). In a recent study conducted by our group, we showed that that chronic treatment with lithium chloride at subtherapeutic concentrations was able to modify the secretion of pro-and anti-inflammatory interleukins in cocultures of cortical and hippocampal neurons with glial cells, and this effect was associated with the preservation of culture integrity (De-Paula et al, 2016b;Goshi et al, 2020). Gene Ontology (GO) is a bioinformatics approach to ascertain and to unify the representations of gene-and gene product attributes across species, focusing on the related functions of these interactions.…”
Section: Introductionmentioning
confidence: 86%
“…A primary rodent tri-culture system of neurons, astrocytes and microglia in serum-free conditions (using TIC-supplemented media) shows promise in modeling different neuroinflammatory scenarios ( 88 ), in line with both in vivo and in vitro studies ( 77 , 89 , 90 ). However, TIC factors could not be omitted in the tri-cultures ( 88 ), indicating that endogenous secretion from the cultured astrocytes was not sufficient to retain a viable and physiologically active microglial phenotype. Interestingly, co-culture with hiPSC-neurons and astrocytes is capable of shifting the transcriptional profile of hiPSC-microglia further towards an ex vivo state than TIC media, although the gap between in vitro and ex vivo microglia is not fully closed ( 29 ).…”
Section: Improving Hipsc-microglia Through Co-culturementioning
confidence: 98%
“…Microglia and astrocytes operate in concert, both possessing that "double-edged sword" capacity to either support neuronal recovery (simplistically, "helpful" M2 and A2 phenotypes) or cause neuronal death ("harmful" M1 and A1 reactive phenotypes) [(77) reviewed by [87)]. A primary rodent tri-culture system of neurons, astrocytes and microglia in serum-free conditions (using TIC-supplemented media) shows promise in modeling different neuroinflammatory scenarios (88), in line with both in vivo and in vitro studies (77,89,90). However, TIC factors could not be omitted in the tri-cultures (88), indicating that endogenous secretion from the cultured astrocytes was not sufficient to retain a viable and physiologically active microglial phenotype.…”
Section: Improving Hipsc-microglia Through Co-culturementioning
confidence: 99%
“…Their potential has been further expanded by the establishment of co-cultures, where multiple cell types are cultured together with the use of semi-permeable membrane inserts. Neuronal co-cultures allow investigation of the interplay between neurons and other different cell types, such as astrocytes [ 16 , 17 ], microglia [ 18 , 19 ], or both in the so-called tri-culture system [ 20 ], up to more complex heterogeneous cultures such as those including neurons, glia, endothelium and glioma cells [ 21 ], or those addressing multi-cellular tissue units, like neurogenic niches [ 22 , 23 ] and the blood–brain barrier (BBB) [ 24 ].…”
Section: Brain-on-chip Biotechnology: a Historical Overviewmentioning
confidence: 99%